The Anterior Chamber Injection of Moxifloxacin Injection to Prevent Endophthalmitis after Cataract Surgery: A Meta-analysis. (25th August 2020) - Wang, Xiao-lei; Huang, Xiao-yong; Wang, Zhen; Sun, Wei
Abstract : Purpose . A meta-analysis was performed to compare the efficacy of an anterior chamber injection of moxifloxacin in the prevention of endophthalmitis after cataract surgery. Methods . A computer-based search of PubMed, Embase, the Cochrane Library, and the Clinical Trial database for articles related to anterior intraventricular injection of moxifloxacin for the prevention of endophthalmitis after cataract surgery was performed through April 2019. Study selection, data exclusion, and quality assessment were performed by two independent observers. Statistical analysis for the meta-analysis was performed by RevMan5.3 software. Results . Eight studies were included, with a total of 123, 819 eyes. The meta-analysis showed that an anterior chamber injection of moxifloxacin can prevent the incidence of endophthalmitis after cataract surgery (OR = 0.29, 95% CI (0.15, 0.56), P = 0.0002 ), and the difference was statistically significant. There were no significant differences between the moxifloxacin injection and nonmoxifloxacin injection groups in regard to UCVA (log MAR) (SMD = −0.13, 95% CI (−0.62, 0.35), P = 0.60 ), BCVA (log MAR) (SMD = −0.27, 95% CI (−1.28, 0.74), P = 0.60 ), IOP (SMD = −0.04, 95% CI (−0.02, 0.01), P = 0.22 ), corneal edema (OR = 1.03, 95% CI (0.23, 4.69), P = 0.97 ), CCT (SMD = −0.01, 95% CI (−0.07, 0.05), P = 0.77 ), or ECD (SMD = 0.00, 95% CI (−0.06, 0.07), P = 0.94 ). Conclusion . An anterior chamber injection of moxifloxacin can effectively prevent the incidence of endophthalmitis after cataract surgery, while the moxifloxacin injection and nonmoxifloxacin injection groups had similar results in regard to UCVA (log MAR), BCVA (log MAR), IOP, corneal edema, CCT, and ECD.